PRZEKONANIA HAMULCEM INNOWACYJNEGO MYŚLENIA - Smuk, Maciej (Neofilolog, 2018)
Beliefs reflect the way we think about different issues, attitudes and behaviours. Many of them are wrong, or – at best – simplified. Beliefs also relate to the didactics of foreign languages. This paper discusses the qualities, sources and consequences of these beliefs and presents the results of research conducted on a group of 434 students regarding beliefs among other individual variables and the process of learning a foreign language.